BIOFILMS AND ANTIBIOTIC RESISTANCE - Tejo Jayadi (Faculty of Medicine Universitas Kristen Duta Wacana, 2021)
The physician and health practitioner’s attention and alertness to biofilm existence and the consequences of biofilm in the biotic and abiotic environment are important to improve hygiene practice, rational antibiotic prescription, controlling the spread and emergence of emergency antibiotic resistance in healthcare facilities and community. The majority of chronic persistence and recurrent infection because of antibiotic resistance is biofilm infection, so needed precision and power alternative approach of management and therapy.